A necessary evil: the Copenhagen School and the construction of migrants as security threats in political elite discourse: a comparative study of Malaysia and Singapore - Thompson, Caryl (2016)
The role of political discourse in the communication of security issues is fundamental to the Copenhagen School’s framework of securitization. In their work, Security: A New Framework for Analysis (1998), the Copenhagen School set out to challenge traditional International Relations theory by questioning the primacy of state-centric approaches that narrowly focus on military aspects of security. Whilst broadening the areas of security to include economic, societal, political and environmental threats, they also proposed that threats are articulated through the “speech acts” of mainly political elites. By signaling threats discursively via “securitizing moves”, political elites inform the audience of the existence of security threats. However, the Copenhagen School fails to address the political partiality of such pronouncements. The focus of this analysis is to examine the persuasive discursive practices employed by political elites to encourage audience consent with a specific focus on political elite portrayals of inward migration in relation to security. In their work, “Identity, Migration and the New Security Agenda in Europe” (1993), the Copenhagen School outlined a nexus between security and transnational migration within a Western context. Using content analysis and critical discourse analysis methods, this analysis will provide a comparative cross-national study of how migration is constituted as a security threat. By analysing political elite discourse as presented in speeches and as recontextualised in media portrayals in two major South East Asian receiving countries, Malaysia and Singapore, this thesis assesses the applicability of the Copenhagen School approach in alternative locations. Adopting a thematic approach, it examines how migrants are depicted via political discourse as threats to societal, economic and political security and how the feminization of migration in recent years has been depicted as a security challenge. A cross-national comparison of political discourse relating to the migrant/security nexus reveals not only how discursive formulations of security by political elites are constructed in order to legitimise policy and practices, but how similar issues may be addressed differently. Both Malaysia and Singapore have a long history of immigration, which is reflected in their diverse multi-ethnic, multi-racial and multi-cultural societies. Geographically co-located and with a shared historical legacy, both have become increasingly dependent on migrant labour to support economic growth and receive relatively large intakes of migrants from neighbouring countries. Yet, there are significant differences in how migrants are depicted in relation to security. Challenges are proposed to the framework that the Copenhagen School propounds. Moreover, I contend that the constructed nature of political discourse allows the potential for a more nuanced and normative discourse that could desecuritize migration and focus more positively on its benefits and upon alternative non-elite perspectives of security.